Efficacy of fluoride associated with nano-hydroxyapatite in reducing enamel demineralization adjacent to orthodontic brackets: in situ study - Carina Faleiros Demito; Julyano Vieira da Costa; Marina de Lourdes Calvo Fracasso; Adilson Luiz Ramos (Dental Press Editora, 2020)
ABSTRACT Objective: To assess in situ the effect of fluoride associated with nano-hydroxyapatite for the prevention of demineralization of the enamel adjacent to orthodontic brackets. Material and Methods: Eight volunteers wore palatal devices prepared with 6 bovine enamel blocks (5x5x2 mm) with bonded brackets. The volunteers used the devices in two different moments of 14 days each. During the first 14 days, a product containing fluoride + nano-hydroxyapatite was applied twice (experimental group, GNH, n = 48), and for the other 14 days no prevention product was applied (control group, CG, n = 48). In both groups, along the experiment, the blocks were dripped with 20% sucrose eight times daily. After the experiment, all the specimens were sectioned and examined for lesion depth analysis (µm) under polarized light microscopy, and for enamel longitudinal microhardness (measured under the bracket, at 30 µm and at 130 µm from the margin), at seven different depths (10, 20, 30, 50, 70, 90, and 110 µm). Results: Under polarized light, group GNH presented significantly less demineralization depth ( X ¯= 15.01 µm, SD = 33.65) in relation to CG ( X ¯= 76.43 µm, SD = 83.75). Enamel longitudinal microhardness demonstrated significantly higher microhardness for group GNH when compared to CG. Conclusion: Fluoride + nano-hydroxyapatite can be an alternative preventive procedure for demineralization of the enamel adjacent to orthodontic brackets.